(untitled) (Pesquisa Odontológica Brasileira, 2002)
Thirty children with AIDS, aging 2 to 6 years, of both genders, treated as outpatients at the hospital Santa Casa de Misericórdia, São Paulo, were evaluated for oral manifestations and compared to a control group of age- and sex-matched healthy subjects. The correlation between oral lesions and the degree of immunosuppression was analyzed. The most prevalent oral manifestations - lymphadenopathy, followed by gingival alterations - were observed in the children with the highest levels of immunosuppression. Other manifestations observed in the AIDS group were: pseudomembranous and erythematous candidosis, enlargement of the parotids and ulcers. The results did not indicate a higher frequency of lesions. However, the observed oral manifestations had an early occurrence, which indicates that the early diagnosis is an important component in the management of those patients.